(untitled) (Indian Journal of Public Health Research & Development, 2021)
Background-Coronavirus disease COVID-19 become the 5th pandemic disease since 1918 which is reported first in Wuhan, China after that its affect all over the world. In India, it is confirmed January 30, 2020. Professionally, also being challenged during this pandemic as we are moving under pressure in new model which involves re-skilling and redeploying staff for intensive care units, also reconsider of standard approaches for assessment and management. All things persist stress which leads to anxiety and depression. Purpose of the study to analyse the prevalence of perceived stress in physiotherapy profession who’s practicing in hospitals, healthcare centres or rehabilitation centres. Methods- Samples collected from online survey and expected sample size more than 30 clinical physiotherapist who’s working in different setups. Perceived stress scale -10 used under the inclusion and exclusion criteria. Inclusion Criteria- must be clinical therapist working in different setups as hospitals, rehabilitation centres, and multispecialty clinics and exclusion criteria is physiotherapist who working in academic field. Analysis carried out by Microsoft Excel 2007. Conclusion-Analysis found prevalence of perceived stress level 13% high, 68% moderate, and 19% low stress in the total respondent physiotherapist.The high prevalence of moderate perceived stress in clinical physiotherapist population which is lies under 18-29 year of age criteria. Study also depicting male perceiving high stress rather female.